Isolation of Nucleic Acids from Different Biological Objects with Silica—Magnetite Nanoparticles - Volkova, N.N.; Derjabin, O.N.; Dudchenko, N.O. (Наносистеми, наноматеріали, нанотехнології, 2008)
Now, modified magnetic particles are widely used in different biological and medical applications (enzyme and protein immobilization, cells separation and purification, MRI, targeted drug delivery, etc.). The aim of the present study is to reveal the ability of synthesized silica-modified magnetic particles to isolate DNA from the biological tissues in comparison with common method used the non-magnetic particles. Magnetite (Fe3O4) particles are prepared via co-precipitation of Fe+2 and Fe+3 with NH4OH in aqueous solution. Silica—magnetite nanocomposites are prepared via tetraethoxysilane hydrolyzation in alcohol—water—ammonia mixture. The average core size of synthesized magnetic nanoparticles is about 15 nm (according to the TEM data). Application of these compounds for DNA isolation from different biological objects showed significant time-savings, overall higher yields, lower RNA contamination and better polymerase chain reaction (PCR) amplification compared to commercial available silica non-magnetic particles (Promega). High efficiency of nucleic-acid purification by silica—magnetite particles is confirmed in molecular assays with reverse transcriptase—polymerase chain reaction (RT—PCR) assays of RNA- and DNA-virus diseases of plants, avian, cattle and estimation of bacterial spectrum in dairy products (probiotics).